RETHINKING RISK GOVERNANCE IN NIGERIAN BANKS - K. Derri, Dr. Damfebo; Abdullahi, A. Y. (IJRDO - Journal of Business Management, 2017)
The banking business by its nature is a high-risk environment. It is risky in the sense that it is the only business where the proportion of borrowed funds is far higher than the owners’ equity. A high level of financial leverage is usually associated with high risk. This can easily be seen in a situation where adverse rumours, whether founded or not would precipitate financial panic and by extension a run on a bank. Few banks are able to withstand a persistent run, even in the presence of a good lender of last resort. As depositors take out their funds, the bank hemorrhages and in the absence of liquidity support, the bank is forced eventually to close its doors. This paper therefore argues that since the success or failure of a bank depends by and large on the effective risk management there is the need for banks board to give greater attention to the risk management function in the management of the bank. The paper further argue that the practice of placing the risk management function under the oversight of the audit committee is untenable having regard to the fact that the risk management committee is a distinct committee of the board and it should be so recognised and empowered to carry out its functions as an independent committee especially so that the risk management function is forward looking in its approach to risk governance whilst the audit function is backward looking in its approach to governance.